2020
DOI: 10.19168/jyasar.633351
|View full text |Cite
|
Sign up to set email alerts
|

Borsa İstanbul Endekslerinde Adaptif Piyasa Hipotezinin Geçerliliğinin Test Edilmesi

Abstract: Çalışmada günlük getiri verileri, iki yıllık alt örneklere ayrılmış ve hisse senedi getirilerinin öngörülebilirliğinin zaman içinde nasıl değiştiğini belirlemek için doğrusal ve doğrusal olmayan testler uygulanmıştır. Otokorelasyon ve runs testlerinden elde edilen sonuçlar, genellikle 3 endeksin etkin ve etkin olmayan dönemler arasında geçiş yaptığını ve dolayısıyla piyasaların Adaptif Piyasa Hipotezi ile uyumlu olduğunu ortaya koymuştur. Varyans oranı testi ile doğrusal olmayan testlerin sonuçları ise hisse s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
3
3
0
1
Order By: Relevance
“…Hence, these may be regarded as the main reasons for the return predictability and inefficient market conditions for the aforementioned period. Similar findings were also obtained in the study of Eyüpoğlu & Eyüpoğlu (2020) in which no sign of market efficiency was observed in 1993. In continuation, following years until 2008 mostly present unpredictable behaviour of stock returns for both of the applied tests.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Hence, these may be regarded as the main reasons for the return predictability and inefficient market conditions for the aforementioned period. Similar findings were also obtained in the study of Eyüpoğlu & Eyüpoğlu (2020) in which no sign of market efficiency was observed in 1993. In continuation, following years until 2008 mostly present unpredictable behaviour of stock returns for both of the applied tests.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies in the literature demonstrate the changing predictability in stock markets. In compliance with the outcomes of AMH examination in this study, it was seen that the return predictability varied over time similar to the studies of Lim (2007), Kim et al (2011), Smith (2012, Ghazani & Araghi (2014), Gyamfi (2018), Eyüpoğlu & Eyüpoğlu (2020) and Obelade & Muzindutsi (2020). Therefore, it can be mentioned that market efficiency cannot be asserted as an all-or-nothing condition for Borsa Istanbul since there have been some periods of obvious predictability and some periods of unpredictability in compliance with the changing market conditions for the period that this study covers.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations